2004
DOI: 10.1200/jco.2004.04.109
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Model of Pulmonary Adenocarcinoma by Expression Profiling of Eight Genes As Determined by Quantitative Real-Time Reverse Transcriptase Polymerase Chain Reaction

Abstract: By analyzing a reasonably small number of genes, patients with adenocarcinoma could be stratified according to their prognosis. The prognostic model could be applicable to future decisions concerning treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
120
1
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(126 citation statements)
references
References 32 publications
4
120
1
1
Order By: Relevance
“…30 Despite this, examples of reliable validation of microarray results by PCR also exist. 31,32 In the present study, we applied real-time Q-PCR to validate cDNA microarray results of Dyrskjøt et al 16 The highly discriminative gene expression pattern of the 26 genes presented by Dyrskjøt et al could not be reproduced. This poor reproducibility may have several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…30 Despite this, examples of reliable validation of microarray results by PCR also exist. 31,32 In the present study, we applied real-time Q-PCR to validate cDNA microarray results of Dyrskjøt et al 16 The highly discriminative gene expression pattern of the 26 genes presented by Dyrskjøt et al could not be reproduced. This poor reproducibility may have several reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have reported a decrease in PTK7 expression levels in metastatic melanoma (25) and clear cell renal cell carcinoma, (26) PTK7 has been shown to be upregulated in many types of human malignancy, including colon cancer, lung carcinoma, liposarcoma, gastric cancer, and acute myeloid leukemia. (11,(17)(18)(19)(20)22) Prebet et al (20) reported that increased expression of PTK7 is correlated with poor clinical outcome in acute myeloid leukemia, a finding that was linked to increased cell migration and resistance to apoptosis. Meng et al (23) showed that knockdown of PTK7 in colon cancer cells inhibits proliferation and induces caspase-10-dependent apoptosis through the mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Increased PTK7 expression has been reported in several types of cancer, including colon cancer, (11,17) gastric cancer, (18) lung cancer, (19) acute myeloid leukemia, (20,21) and liposarcoma. (22) Expression of PTK7 in leukemia cells enhances cell migration and survival.…”
mentioning
confidence: 99%
“…The TaqMan probes (Hs01070032_ m1 Jag1, Hs00171432_m1 Jag2, Hs00194509_m1 Dll1, Hs01085096_m1 Dll3, Hs00184092_m1 Dll4, Hs00172878_m1 Hes1, Hs01062014_m1 Notch1) and the TaqMan Assay kit (all from Applied Biosystems; Thermo Fisher Scientific, Inc.) were used to perform PCR. The expression of the above-mentioned genes [by the change-in-cycling-threshold ΔCq method (18,19)] were calculated and normalized to ribosomal 18SRNA gene expression (Hs99999901_s1 18SRNA). The following thermocycling conditions were used: 50˚C for 2 min; 95˚C for 10 min; 40 cycles of 95˚C for 15 sec and 60˚C for 60 sec.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%